TAX TRAINING AND THE RISE OF FISCAL AWARENESS AMONG SMALL ENTREPRENEURS: EVIDENCE FROM MEDAN PETISAH INDONESIA - Ifan Setia Sastra Waruwu; Adanan Silaban; Amran Manurung (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2025)
This study aims to examine the effect of tax training on tax awareness among small business entrepreneurs in the working area of KPP Medan Petisah. Employing a quantitative research design, data were collected through structured questionnaires distributed to a representative sample of small business taxpayers. The data were analyzed using multiple linear regression to determine the relationship between tax training and tax awareness. The results indicate that tax training has a significant and positive impact on enhancing tax awareness. Specifically, well-structured and contextualized training programs improve taxpayers’ understanding of their rights and obligations, reduce reporting errors, and foster positive perceptions toward the tax system. These findings corroborate previous research highlighting the critical role of tax education in promoting voluntary compliance and building trust in tax authorities. The study suggests that tax offices should regularly conduct tailored training sessions, incorporating practical topics such as tax reporting procedures and e-filing applications, delivered through both face-to-face and online platforms to maximize outreach and effectiveness.